Under Lock & Skeleton Key: Secret Staircase Mystery #1 - Pandian, Gigi, 1975- (New York : Minotaur Books, 2022)
"Known for her wonderfully addictive characters, multiple award-winning author Gigi Pandian introduces her newest heroine in this heartfelt series debut. Under Lock & Skeleton Key layers stunning architecture with mouthwatering food in an ode to classic locked-room mysteries that will leave readers enchanted. An impossible crime. A family legacy. The intrigue of hidden rooms and secret staircases. After a disastrous accident derails Tempest Raj's career, and life, she heads back to her childhood home in California to comfort herself with her grandfather's Indian home-cooked meals. Though she resists, every day brings her closer to the inevitable: working for her father's company. Secret Staircase Construction specializes in bringing the magic of childhood to all by transforming clients' homes with sliding bookcases, intricate locks, backyard treehouses, and hidden reading nooks. When Tempest visits her dad's latest renovation project, her former stage double is discovered dead inside a wall that's supposedly been sealed for more than a century. Fearing she was the intended victim, it's up to Tempest to solve this seemingly impossible crime. But as she delves further into the mystery, Tempest can't help but wonder if the Raj family curse that's plagued her family for generations-something she used to swear didn't exist-has finally come for her"--.
Keywords: Murder -- Fiction; Family-owned business enterprises; East Indian Americans; Detective and mystery stories; Investigations; Blessing and cursing -- Fiction; Cozy mystery stories; California; Novels; Cozy mystery fiction